(untitled) (Journal of the College of Basic Education, 2026)
The present study investigates the impact of the Lorsbach Model on the achievement and cognitive abilities of students at the Institute of Fine Arts in the subject of Aesthetic Education and Artistic Appreciation. The researcher formulated two null hypotheses denying the presence of statistically significant differences between the experimental and control groups in the post-test. The sample consisted of 24 students, with 12 students in each group, selected from the Department of Plastic Arts. A quasi-experimental design with post-testing was adopted. The experimental group was taught using the Lorsbach Model, while the control group received instruction through traditional methods, after ensuring equivalence in variables such as age, intelligence, and cognitive abilities. The experiment lasted for eight weeks and included eight instructional units. The researcher constructed a 30-item multiple-choice achievement test, which was reviewed by a panel of experts, and its validity and reliability were verified using various statistical tools (Mann–Whitney test, Pearson correlation, Kuder-Richardson 20, among others). The results showed that the experimental group outperformed the control group in both achievement and cognitive development. The study concluded that the Lorsbach Model enhances motivation and willingness to learn, promotes interaction and the generation of mental imagery, which leads to meaningful learning and better application. The researcher recommended adopting the model in art education and conducting training workshops for teachers. Further suggestions included employing the model to develop students’ skills in art criticism and extending its application to other theoretical subjects.